INFLUENCE OF CHANGING PORTRAYALS OF WOMEN IN HINDI CINEMA ON YOUTH’S PROGRESSIVE GENDER ATTITUDES - Agarwal, Aditi; Kumar, Pradeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the impact of evolving portrayals of women in Hindi cinema on the progressive gender attitudes of contemporary youth. In recent decades, Hindi cinema has increasingly shifted from portraying women primarily in conventional and submissive positions to presenting them in more forward-thinking and active roles. The objective of this study is to examine the impact of these alterations in cinematic portrayals on the perceptions and attitudes of young individuals towards gender equality. Through the use of a mixed-methods methodology including quantitative surveys and qualitative interviews, this study examines the relationship between film depictions and changes in gender attitudes among young people. Empirical evidence suggests that favourable depictions of women in contemporary Hindi film are linked to more progressive gender perspectives among young people, underscoring the capacity of media to influence society standards and behaviours.